Analisis Dampak Hambatan Samping Terhadap Tingkat Pelayanan Jalan Kota Makassar - Rimarya Kristanti; Rais Rachman; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2020)
The side obstacle factor is one of the causes of traffic congestion which can affect the level of service of a road. Where congestion is a traffic flow problem caused by an increase in the volume of vehicles on a road section and by side obstacles. The aim is to determine the traffic flow and the impact of side obstacles on the degree of saturation on the Perintis Kemerdekaan road km.8 using the Indonesian Road Capacity Manual (MKJI) in 1997. Based on the calculation and analysis of data obtained the largest traffic flow on Monday, namely 1686.41 SMP / hour, the biggest side obstacle on Saturday is 502.4 and the highest degree of saturation is obtained on Monday afternoon at 0.78 which is where the flow is close to unstable at certain peak hours where the greater the side obstacles the greater the degree of saturation.